DIGITALIZATION OF THE COURT AS AN EFFORT TO REALIZE THE PRINCIPLES OF SIMPLE, FAST, AND LOW-COST COURT PROCEDURES - Dahlan Dahlan; Dian Mustika Intan; Ayu Efritadewi; Taruna Prakarsa (Law Faculty of Universitas Bandar Lampung, 2026)
The development of information technology has driven a transformation in the Indonesian justice system through the implementation of digitalization of judicial services. This study aims to analyze the extent of digitalization of the judiciary, particularly through the implementation of digitalization.e-Court And e-Litigation, capable of realizing the principles of simple, fast, and low-cost justice as mandated by Law Number 48 of 2009 concerning Judicial Power. The research uses a normative juridical method with a statutory, conceptual, and analytical approach. Data were obtained from laws and regulations, court decisions, and relevant scientific literature. The results of the study indicate that the digitalization of justice has made a significant contribution to the efficiency of case administration, acceleration of trial processes, reduction of transportation and administrative costs, and increased public access to judicial services. However, its implementation still faces various obstacles, including the digital infrastructure gap, low technological literacy among some members of the public, and challenges related to security and personal data protection. Therefore, strengthening regulations, increasing human resource capacity, and equalizing technological infrastructure are needed to support the realization of an effective, inclusive, and equitable digital justice system.